Actors and their roles for improving resilience of farming systems in Europe - Bárbara Soriano; Alberto Garrido; Daniele Bertolozzi-Caredio; Francesco Accatino; Federico Antonioli; Vitaliy Krupin; Miranda P.M. Meuwissen; Franziska Ollendorf; Jens Rommel; Alisa Spiegel; Monica Tudor; Julie Urquhart; et al. (Journal of Rural Studies, 2023)
Finding pathways to enhance the resilience of farming systems (FSs) in Europe is key, given the increasing challenges threatening them. FSs are complex socio-ecological systems in which social and ecological components are strongly linked. Social actors have the capacity to shape the FSs' resilience, but there is a knowledge gap about how they can best do it. The aim of this paper is to analyse the roles played by the actors in FSs when dealing with challenges and assess how these roles may contribute to the resilience attributes (conditions that enable resilience) and resilience capacities (robustness, adaptability, and transformability). To this end, ten focus groups have been conducted across FSs in Europe. Results suggest that each actor in the FSs can shape and strengthen different resilience attributes which in turn result in combinations of resilience capacities that are specific to the FS. Thus, enabling resilience is best accomplished with actors taking different roles and jointly configuring the most adequate combination of capacities, which differs across FSs. This paper provides a set of resilience-enabling roles that delineate the pathways to make FSs more resilient. The diversity of actors and resilience-enabling pathways require flexible, coordinated and comprehensive policies that encompass the complexity of the socio-ecological systems.
Keywords: 630; socio-ecological systems; multi-factor approach; focus groups; agriculture; resilience attributes; resilience capacities